Deep learning concepts, methodologies, tools, and applications (Engineering Science Reference, an imprint of IGI Global, 2020)
"This book is a vital reference source that trends in data analytics and potential technologies that will facilitate insight in various domains of science, industry, business, and consumer applications. It also explores the latest concepts, algorithms, and techniques of deep learning and data mining and analysis"--